Mutagenicity of anthraquinone and hydroxylated anthraquinones in the Ames/Salmonella microsome system. - Liberman, D F (1982)
The mutagenicity of anthracene, anthraquinone, and four structurally similar compounds of each was evaluated in the Ames/Salmonella microsome assay. Anthraquinone was shown to be mutagenic for strains TA1537, TA1538, and TA98 in the absence of rat liver homogenate. The four anthraquinone derivatives tested were mutagenic for TA1537 exclusively. None of the anthracenes exhibited mutagenic activity.